Infrared Evanescent Wave Sensing Based on a Ge10As30Se40Te20 Fiber for Alcohol Detection - Zijian Li; Yongkun Zhao; Tianxiang You; Jihong Zhu; Mengling Xia; Ping Lu; Xianghua Zhang; Yinsheng Xu (Sensors, 2023)
Infrared evanescent wave sensing based on chalcogenide fiber is an emerging technology for qualitative and quantitative analysis of most organic compounds. Here, a tapered fiber sensor made from Ge10As30Se40Te20 glass fiber was reported. The fundamental modes and intensity of evanescent waves in fibers with different diameters were simulated with COMSOL. The 30 mm length tapered fiber sensors with different waist diameters, 110, 63, and 31 μm, were fabricated for ethanol detection. The sensor with a waist diameter of 31 μm has the highest sensitivity of 0.73 a.u./% and a limit of detection (LoD) of 0.195 vol.% for ethanol. Finally, this sensor has been used to analyze alcohols, including Chinese baijiu (Chinese distilled spirits), red wine, Shaoxing wine (Chinese rice wine), Rio cocktail, and Tsingtao beer. It is shown that the ethanol concentration is consistent with the nominal alcoholicity. Moreover, other components such as CO2 and maltose can be detected in Tsingtao beer, demonstrating the feasibility of its application in detecting food additives.